Redesign of accounting education to meet the challenges of artificial intelligence: A literature review - Valeriu Brabete; Cătălin Mihail Barbu; Daniel Cîrciumaru; Daniel Goagără; Dorel Berceanu (Amfiteatru Economic, 2024)
The development of emerging technologies, including artificial intelligence (AI), has a direct impact on the accounting profession in the sense of redefining the role and place that accounting specialists occupy within economic entities. This paper is a systematic literature review and aims to emphasise and synthesise the main challenges regarding the impact that artificial intelligence and other related technologies exert on accounting professionals and the competencies they need to develop or acquire. At the same time, the outline of specific solutions was envisaged, through which accounting professionals can be supported in their efforts to adapt to the new requirements of the labour market imposed by the evolution of disruptive technologies. To achieve the proposed objectives, Web of Science (WoS) was used as an academic database and specific tools for bibliometric analyses, including the VOSviewer application. The results identify universities as the main pillar in the process of the redesign of accounting education, and update of the curriculum in the field as the main measure to be undertaken. The originality of the paper resides in the identification of specific solutions for curriculum reconfiguration in the field of accounting education, the highlighting and overcoming of possible challenges for the redesign of the education process in the field of accounting, under the impact of AI.
Keywords: I20; J24; M40; N30; O33; 330; accounting profession; artificial intelligence; digitalization; professional competencies; accounting curriculum; accounting education